1983
DOI: 10.1002/kin.550150607
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the gas‐phase reaction CH3F + I2 ⇆ CH2FI + HI: The CH bond dissociation energy in methyl and methylene fluorides

Abstract: The kinetics of the gas-phase reaction of CH3F with 12 have been studied spectrophotometrically from 629 to 710 K, and were determined to be consistent with the following mechanism:(KIJ The enthalpy change at 298 K was combined with selected thermochemical data to derive DH"(CH2F-H) = 101.2 f 1 kcal/mol *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…The derived C-H bond dissociation energies show the well-accepted trend of decreasing bond strength with bromine substitution, a trend that is also observed with chlorine substitution but just the opposite of which is seen with fluorine substitution. 55,56,62,63 There is some difference in our derived C-Br bond dissociation energies for CH 2 Br 2 and CHBr 3 from values reported in the literature, with our values being lower by approximately 2 and 3 kcal/mol, respectively. The derived DH°(CH 2 Br-Br) ) 69.8 ( 2 kcal/mol by Tschuikow-Roux and Paddison 55 is too high because, as pointed out earlier, they adopted the estimated ∆H°f ,298 (CH 2 Br 2 ,g) of Bickerton et al 53 Furuyama et al 58 have already pointed out that the DH°-(CHBr 2 -Br) ) 66 ( 4 kcal/mol reported by Miller and Palmer 61 is too high, and in fact in their analysis adopted the minimum value of 62 kcal/mol.…”
Section: H°-h°0 (Kcal Molcontrasting
confidence: 70%
“…The derived C-H bond dissociation energies show the well-accepted trend of decreasing bond strength with bromine substitution, a trend that is also observed with chlorine substitution but just the opposite of which is seen with fluorine substitution. 55,56,62,63 There is some difference in our derived C-Br bond dissociation energies for CH 2 Br 2 and CHBr 3 from values reported in the literature, with our values being lower by approximately 2 and 3 kcal/mol, respectively. The derived DH°(CH 2 Br-Br) ) 69.8 ( 2 kcal/mol by Tschuikow-Roux and Paddison 55 is too high because, as pointed out earlier, they adopted the estimated ∆H°f ,298 (CH 2 Br 2 ,g) of Bickerton et al 53 Furuyama et al 58 have already pointed out that the DH°-(CHBr 2 -Br) ) 66 ( 4 kcal/mol reported by Miller and Palmer 61 is too high, and in fact in their analysis adopted the minimum value of 62 kcal/mol.…”
Section: H°-h°0 (Kcal Molcontrasting
confidence: 70%
“…However, PVF is amorphous in nature, whose structure is (CHF–CH 2 ) n . , The lifetime of polymer is determined by the cavity or trap that occurred with the electron avalanches. The C–F bond is stronger than the C–H bond. Typically, the bond dissociation energy for C–F is about 119.5 kcal/mol compared with 103.2 kcal/mol for the C–H bond, where the C–F bond is probably 16.3 kcal/mol stronger than the C–H bond . The consequence is that the C–F bonds are more resistant to radical-induced scission than the C–H bonds.…”
Section: Resultsmentioning
confidence: 99%
“…McMillen and Golden estimate the heat of formation of the CF 2 H radical at 0 K to be −59.2 ± 5 kcal mol -1 . Pickard and Rodgers have experimentally derived the heat of formation value at 298 K for CF 2 H as −57.1 ± 1 kcal mol -1 . To evaluate the heat of formation for CF 2 H, two isodesmic reaction schemes are used.…”
Section: Resultsmentioning
confidence: 99%